Cylindroma of the breast: a case report and review of the literature - O'Sullivan Martin J; Hill David H; Mahmoud Amr; Bennett Michael W (BMC, 2009)
Abstract Cylindroma of the breast is a very rare lesion which is morphological and immunophenotypically identical to benign dermal cylindroma. We report a breast cylindroma in a previously healthy 62 year old female detected through a national breast screening program. The patient had no significant family or past medical history, and specifically no history of breast or skin diseases. The tumor consisted of well circumscribed islands of epithelial cells surrounded by a dense membrane material, and focally containing hyaline globules. At low power the islands of tumour cells formed a "jig-saw" pattern, which is typical of cylindroma, but was present within normal breast parenchyma and no had direct connection with the overlying skin. Two distinct cell populations, smaller peripheral basaloid cells and larger central cells with vesicular chromatin, were highlighted by immunohistochemistry for p63 and cytokeratin-7 respectively. Immunohistochemistry for ER, PR, and Her2/neu was negative in tumour cells. We discuss the nine previously reported cases and the distinction of breast cylindroma from adenoid cystic carcinoma, the main differential diagnosis.